Stock Market Returns, Corporate Governance and Capital Market Equilibrium - Bruno Maria Parigi; Loriana Pelizzon; Ernst-Ludwig von Thadden (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper proposes a theoretical model that incorporates corporate governance into the basic CAPM, where corporate governance affects the disutility of managerial effort and the possibility of managers to divert company resources. It shows that corporate governance affects firms' stock returns and also how the quality of corporate governance is chosen endogenously. The model predicts that in equilibrium the quality of corporate governance correlates positively with â and idiosyncratic volatility and negatively with returns on assets. Various tests with U.S. firm data using the corporate governance index of Gompers, Ishii, and Metrick (2003) confirm these predictions.
Keywords: G32; G38; K22; 330; corporate governance; CAPM; variability of returns